2019
DOI: 10.3389/fcimb.2018.00438
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Screen Identifies Unconventional Drugs With Activity Against Multidrug Resistant Acinetobacter baumannii

Abstract: Antibiotic-resistant nosocomial infections are an emerging public health issue; carbapenem-resistant gram-negative bacteria such as Acinetobacter baumannii are among the pathogens against which new therapeutic agents are desperately needed. Drug repurposing has recently emerged as an alternative approach to rapidly identifying effective drugs and drug combinations to combat drug resistant bacteria. We performed a drug repurposing screen against a highly virulent, multidrug resistant, Acinetobacter baumannii st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Developing a new chemical entity drug and delivering it to the market, known as de novo drug discovery, is a time-consuming and expensive process with increasing regulatory requirements and a high risk of failure-all of which could make the pharmaceutical industry a less desirable choice for investors. Nowadays, drug repurposing has become a successful strategy to fast-track therapeutic agents for the treatment of several emerging or rare diseases, such as AIDS, Alzheimer's disease and cancer [10,[34][35][36][37][38][39][40], but also infections with multidrug-resistant strains of clinically relevant pathogens [9,[41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Developing a new chemical entity drug and delivering it to the market, known as de novo drug discovery, is a time-consuming and expensive process with increasing regulatory requirements and a high risk of failure-all of which could make the pharmaceutical industry a less desirable choice for investors. Nowadays, drug repurposing has become a successful strategy to fast-track therapeutic agents for the treatment of several emerging or rare diseases, such as AIDS, Alzheimer's disease and cancer [10,[34][35][36][37][38][39][40], but also infections with multidrug-resistant strains of clinically relevant pathogens [9,[41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…One year ago, Cheng et al [73] used an A. baumannii strain resistant to most antibiotics (AB5075) and reported that 3 antineoplastics (5-fluorouracil, 6-thioguanine and pifithrin-μ), an anti-rheumatic (auranofin), an antipsychotic (fluspirilene), an anti-inflammatory (Bay 11-7082) and an alcohol detergent (disulfiram) inhibited the growth of a MDR A. baumannii. 5-fluorouracil and 6-thioguanine seemed to be the best candidates among all the repurposed drugs in the treatment of MDR clinical A. baumannii: their IC90 values and MIC were lower than standard plasma drug concentration levels in human, suggesting a possible use without major adverse events.…”
Section: Anti-cancerous Drugs As Antibacterialsmentioning
confidence: 99%
“…These screens resulted in the discovery of many antibiotics exhibiting both broad spectrum, such as streptomycin (19), and mycobacterium-specific activity, including isoniazid, pyrazinamide, ethionamide, ethambutol (4), and bedaquiline (20). Recently, Gramspecific (21)(22)(23)(24) and pathogen-specific (25,26) antibiotic discovery were also proven to be successful, leading to the identification of narrow spectrum compounds, including some that are active only against A. baumannii (27)(28)(29). As more candidate compounds are revealed through screening, there will be a need for better methods to elucidate their mechanism of action (MOA) in A. baumannii.…”
mentioning
confidence: 99%